2017
DOI: 10.1093/geront/gnx111
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-National Study of the Gender Gap in Health Among Older Adults in India and China: Similarities and Disparities

Abstract: In these study populations, major sociodemographic and health risk characteristics accounted for very small parts of the gender differences in health, except in cognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 42 publications
6
30
1
1
Order By: Relevance
“…These findings are consistent with previous studies examining aging using a cultural lens [20,21,22]. This study adds to the body of work about how cultural similarity in various aspects of aging and the associations between factors are consistent between eastern and western countries [37] and as reported by [27], the present data also suggests older adults have similar concerns about aging, but not all have the exact same concern.…”
Section: Cultural Uniformity Of the Aging Experiencesupporting
confidence: 92%
See 2 more Smart Citations
“…These findings are consistent with previous studies examining aging using a cultural lens [20,21,22]. This study adds to the body of work about how cultural similarity in various aspects of aging and the associations between factors are consistent between eastern and western countries [37] and as reported by [27], the present data also suggests older adults have similar concerns about aging, but not all have the exact same concern.…”
Section: Cultural Uniformity Of the Aging Experiencesupporting
confidence: 92%
“…The authors also point out that their multinational findings are consistent with findings from Western countries. Of particular interest, Oksuzyan et al [27] indicate similar concerns exist for older adults as reported by younger adult, however, not everyone over the age of 65 reports the same exact type of concerns. Therefore, although differences have been reported by prior studies with regard to aging similarity also exists.…”
Section: Collectivist and Individualist Culturesmentioning
confidence: 93%
See 1 more Smart Citation
“…The two studies found that women had lower grip strength than men 8,9 . Similarly, other cross-national comparison studies have shown that men are physically stronger 8,10,11 and have higher grip strength measures than women [12][13][14] . However, comparisons of grip strength across different populations have been impeded due to the use of different measurement tools and methods, and little is known about grip strength in the oldest population 15 .…”
Section: Introductionmentioning
confidence: 72%
“…Previous literature has reported that some of the gender gap in various cognitive measures is explained by differences in education 1,13,32 . In this study, we found that a slightly higher proportion of women than men in Northern Europe had high education, which may partially explain the fact that the gender difference in cognition was greatest in this region.…”
Section: Discussionmentioning
confidence: 99%